The Factors of Millennials’ Continuance Intention to Use Digital Wallets in Indonesia - Yasintha Soelasih; Sumani (Binus Business Review, 2022)
The growth of digital wallets increases the convenience of consumers in making transactions. The convenience that consumers feel in using digital wallets further increases their consumption. Companies influence the age group, such as millennials, with high potential in using digital wallets. The research emphasized the consumer behavior of millennials in using digital wallets. The study aimed to examine the variables that affected digital wallet users in terms of perceived usefulness, perceived risk, customer attitude, customer satisfaction, and continuance intention to use. The questionnaire was distributed using the G-form using the determination of respondents by purposive sampling. The number of respondents was 276. The measurement of reliability and validity used loadings values, Cronbach’s alpha, Composite Reliability (CR), Average Variance Extracted (AVE), and discriminant validity. In measuring the fit model, the Standardized Root Mean Square Residual (SRMR) value was used. Then, the research used Partial Least Square-Structural Equation Model (PLS-SEM) to test the hypothesis. The results show that perceived usefulness affects customer attitudes toward using digital wallets. Meanwhile, perceived risk has no effect on customer attitudes. Customer attitude impacts customer satisfaction and continuance intention to use digital wallet users directly and indirectly. Moreover, millennials strengthen the influence of customer attitude on continuance intention to use. The effect is negative, meaning that if the age of the millennials increases, it will cause a decreased attitude change towards continuance intention to use digital wallets.